Housing Provision System and Residential Emancipation: analysis of the public effort in housing in Spain and its effect on emancipation opportunities from a comparative regional perspective - Echaves García, Antonio; Navarro Yañez, Clemente Jesús (Política y Sociedad, 2018)
Housing Provision Systems can be defined as public and private initiatives that configure the options available in each society to provide a place to reside. From this perspective, it should be considered as a central element of the Welfare States, along with employment policies, health or education. In fact, comparative analyzes between countries show housing provision systems that correspond to classifications of welfare regimes and have effects on access to housing, the predominant form of housing regime and their conditions. In these researches, Spain, usually classified as a dualist model that promotes housing ownership over rental, as opposed to the integrated model more characteristic of northern European countries. In this way, this article develops two objectives. On the one hand, show the existence of Autonomous Systems of Housing Provision in Spain, proposing indicators in this regard. On the other hand, it aims to show the effects on residential emancipation of young people, using data from different statistical sources (Housing Census, Spanish Labour Force Survey and other Spanish secondary data sources). Thus, it is an analytical and empirical proposal about an aspect scarcely studied of sub-national welfare systems.